Length of Stay Beyond Medical Readiness in a Neurosurgical Patient Population and Associated Healthcare Costs. Issue 3 (28th December 2020) - Linzey, Joseph R; Foshee, Rachel; Moriguchi, Francine; Adapa, Arjun R; Koduri, Sravanthi; Kahn, Elyne N; Williamson, Craig A; Sheehan, Kyle; Rajajee, Venkatakrishna; Thompson, B Gregory; Muraszko, Karin M; Pandey, Aditya S
Abstract: BACKGROUND: Length of stay beyond medical readiness (LOS-BMR) leads to increased expenses and higher morbidity related to hospital-acquired conditions. OBJECTIVE: To determine the proportion of admitted neurosurgical patients who have LOS-BMR and associated risk factors and costs. METHODS: We performed a prospective, cohort analysis of all neurosurgical patients admitted to our institution over 5 mo. LOS-BMR was assessed daily by the attending neurosurgeon and neuro-intensivist with a standardized criterion. Univariate and multivariate logistic regressions were performed. RESULTS: Of the 884 patients admitted, 229 (25.9%) had a LOS-BMR. The average LOS-BMR was 2.7 ± 3.1 d at an average daily cost of 9 148.28 ± 12 983.10, which resulted in a total cost of 2 076 659.32 over the 5-mo period. Patients with LOS-BMR were significantly more likely to be older and to have hemiplegia, dementia, liver disease, renal disease, and diabetes mellitus. Patients with a LOS-BMR were significantly more likely to be discharged to a subacute rehabilitation/skilled nursing facility (40.2% vs 4.1%) or an acute/inpatient rehabilitation facility (22.7% vs 1.7%, P < .0001). Patients with Medicare insurance were more likely to have a LOS-BMR, whereas patients with private insurance were less likely ( P = .048). CONCLUSION: The most common reason for LOS-BMR was inefficient discharge of patients to rehabilitation and nursing facilities secondary to unavailability of beds at discharge locations, insurance clearance delays, and family-related issues.